Balloon mitral valvuloplasty saving a pregnant woman with mitral stenosis, pulmonary oedema and infective endocarditis. Issue 13 (2013) - Hassine, M; Cheniti, G; Kehla, S Ben; Mahjoub, M
No abstract available